Pengaruh Implementasi Digital Payment Dan Literasi Digital Terhadap Peningkatan Efisiensi Transaksi (Studi Kasus Pada Pedagang Dan Pembeli Di Pasar Tumpang) - Putri, Cici Amelia; Wahono, Budi; Sholehuddin, Sulton (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to explore and explain the impact of the implementation of digital payments and digital literacy on transaction efficiency, focusing on traders and buyers at Tumpang Market. By using a quantitative approach and applying the Malhotra formula to determine the sample size of this study, because the total population is still uncertain. Based on the calculation of this formula, the sample consists of 85 respondents. To answer the research questions, using SPSS for various analyses, including normality tests, classical assumption tests, hypothesis testing, multiple linear regression, and adjusted R² coefficient tests. The research findings reveal that the implementation of digital payments and digital literacy simultaneously significantly affect transaction efficiency. Keywords: Implementation of Digital payment, Digital Literacy, Transaction Efficiency